Soft Simply Connected Spaces And Soft Simply Paracompact Spaces. (July 2020) - Noori, S.; Yousif, Y. Y.
Abstract: We introduce in this paper some new concepts in soft topological spaces such as soft simply separated, soft simply disjoint, soft simply division, soft simply limit point and we define soft simply connected spaces, and we presented soft simply Paracompact spaces and studying some of its properties in soft topological spaces. In addition to introduce a new types of functions known as soft simply pu -continuous which are defined between two soft topological spaces.